2021
DOI: 10.1186/s13014-021-01942-y
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of sliding window and field-in-field techniques for tangential whole breast irradiation using the Halcyon and Synergy Agility systems

Abstract: Background To implement a tangential treatment technique for whole breast irradiation using the Varian Halcyon and to compare it with Elekta Synergy Agility plans. Methods For 20 patients two comparable treatment plans with respect to dose coverage and normal tissue sparing were generated. Tangential field-in-field treatment plans (Pinnacle/Synergy) were replanned using the sliding window technique (Eclipse/Halcyon). Plan specific QA was performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 21 publications
(34 reference statements)
0
6
0
1
Order By: Relevance
“…have shown that fast, safe, and effective treatment delivery is possible with Halcyon RDS for conventionally fractionated daily treatment for head and neck, whole breast, and prostate. Moreover, many other researchers have demonstrated the clinical feasibility of using Halcyon RDS for the conventional daily treatment of whole breast patients using either a dynamically flattened beam (DFB) or FFF beam with tangential fields or field‐in‐field approach including bilateral breast 7–14 . Our study is to complement those previous investigations and is the first to benchmark on the evaluation and clinical implementation of Halcyon RDS for the hypofractionated Fast‐Forward trial for APBI patients.…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…have shown that fast, safe, and effective treatment delivery is possible with Halcyon RDS for conventionally fractionated daily treatment for head and neck, whole breast, and prostate. Moreover, many other researchers have demonstrated the clinical feasibility of using Halcyon RDS for the conventional daily treatment of whole breast patients using either a dynamically flattened beam (DFB) or FFF beam with tangential fields or field‐in‐field approach including bilateral breast 7–14 . Our study is to complement those previous investigations and is the first to benchmark on the evaluation and clinical implementation of Halcyon RDS for the hypofractionated Fast‐Forward trial for APBI patients.…”
Section: Introductionmentioning
confidence: 77%
“…Moreover, many other researchers have demonstrated the clinical feasibility of using Halcyon RDS for the conventional daily treatment of whole breast patients using either a dynamically flattened beam (DFB) or FFF beam with tangential fields or field-in-field approach including bilateral breast. [7][8][9][10][11][12][13][14] Our study is to complement those previous investigations and is the first to benchmark on the evaluation and clinical implementation of Halcyon RDS for the hypofractionated Fast-Forward trial for APBI patients. In this technical report, we have evaluated plan quality, treatment delivery efficiency, and accuracy of APBI on Halcyon by benchmarking with high-quality APBI treatments that were delivered on our SBRT-dedicated TrueBeam.…”
Section: Introductionmentioning
confidence: 86%
“…Current MLCs typically feature a single layer 19 ; however, multilayer MLCs have been gradually introduced to clinical settings 25,27 . Multilayer MLCs offer several important advantages, such as reducing normal organ dose outside the target volume, and requiring less time and fewer monitor units 10,19,28–30 . Although dual‐layer micro‐MLC (DmMLC) uses an orthogonal dual‐layer design, there are two main differences between the DmMLC and αMLC.…”
Section: Discussionmentioning
confidence: 99%
“…Current MLCs typically feature a single layer [18]; however, multilayer MLCs have been gradually introduced to clinical settings [23,24]. Multilayer MLCs have several important advantages, such as reducing normal organ dose outside the target volume, less time and monitor units [10,18,[25][26][27].…”
Section: Discussionmentioning
confidence: 99%